2000
DOI: 10.1002/1529-0131(200011)43:11<2523::aid-anr20>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of osteoclast differentiation factor in rheumatoid arthritis

Abstract: The present results suggest that activated RASF, by expressing ODF, play an important role in rheumatoid bone destruction. Moreover, the data provide evidence that RASF not only activate osteoclasts, but also contribute directly to osteoclastogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
133
1
6

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(143 citation statements)
references
References 24 publications
3
133
1
6
Order By: Relevance
“…Since the RANKL/RANK/ OPG system has been shown to be important in inflammation-induced bone resorption, including that in rheumatoid arthritis (27)(28)(29)46) and in periodontal disease (4,31), we focused on these molecules. Since RANKL mRNA expression in the MG-63 cells was scarce, we used neonatal mouse calvarial bones for these experiments, the rationale being that activation of BK receptors synergistically potentiates IL-1-induced bone resorption in the calvarial bones (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the RANKL/RANK/ OPG system has been shown to be important in inflammation-induced bone resorption, including that in rheumatoid arthritis (27)(28)(29)46) and in periodontal disease (4,31), we focused on these molecules. Since RANKL mRNA expression in the MG-63 cells was scarce, we used neonatal mouse calvarial bones for these experiments, the rationale being that activation of BK receptors synergistically potentiates IL-1-induced bone resorption in the calvarial bones (11).…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in OPG exhibit abundant osteoclasts and an osteoporotic phenotype. RANKL is expressed in synovial tissue from patients with rheumatoid arthritis (27)(28)(29) and has been found to be crucial for osteoclast formation and bone loss in experimentally induced arthritis in mice (30). RANKL is also expressed in gingival tissue from patients with periodontal disease (31,32), and increased RANKL/OPG is associated with bone loss in periodontitis (4,31).…”
mentioning
confidence: 99%
“…In contrast, RANKL is not expressed in normal synovium, suggesting a link between the expression of RANKL mRNA and development of synovial lesions in RA (7). RANKL is expressed by lymphocytes, macrophages, and, in RA, also by synovial fibroblasts (57). RA synovial fibroblasts therefore appear to be additional sources for RANKL (18).…”
Section: Rank/rankl/opg and Ramentioning
confidence: 95%
“…In this regard, it has been shown that the induction of TRAP-positive multinucleated osteoclasts derived from peripheral blood mononuclear cells depends on the level of RANKL produced by cultured RA synovial fibroblasts (57). Moreover, expression of RANKL at sites of bone destruction has been found to be strongest in both osteoclasts and synovial fibroblasts (57,58).…”
Section: Rank/rankl/opg and Ramentioning
confidence: 99%
“…Tumor necrosis factor (TNF) is a key cytokine in RA (6), and selective overexpression of TNF in mice is sufficient for the development of destructive arthritis (7). Of note, synovial fibroblasts and lymphocytes drive the differentiation of osteoclasts from monocyte precursor cells via the expression of RANKL (8)(9)(10)(11). Osteoclasts are cells that are specifically designed to resorb bone (12).…”
mentioning
confidence: 99%